Sophisticated Nickel-Based Nanocatalysts for Effective Hydrogen Evolution Reaction: Preparation, Characteristics, and Electrocatalytic Activity - Alaa N. Kurdi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Hydrogen generated through electrochemical water splitting is a promising clean energy carrier due to its high energy density and carbon-free combustion. Specific Background: The hydrogen evolution reaction (HER) requires efficient cathode catalysts, but platinum-group metals are limited by scarcity and cost, encouraging the exploration of nickel-based electrocatalysts. Knowledge Gap: The relationship between synthesis strategy, nanostructure formation, and HER electrocatalytic behavior of advanced nickel heterostructures and phosphosulfide systems remains insufficiently clarified. Aims: This study evaluates Ni/Ni(OH)₂ heterostructures and nickel phosphosulfide (Ni-P-S) nanocatalysts by examining their preparation, structural characteristics, and HER performance in alkaline media. Results: Structural analysis using XRD, XPS, and TEM confirmed successful nanostructure formation, including core–shell Ni/Ni(OH)₂ structures and porous nanosheet Ni-P-S networks. Electrochemical measurements showed that Ni-P-S required an overpotential of 78 mV at 10 mA cm⁻² and maintained stability for more than 50 hours in 1 M KOH, while Ni/Ni(OH)₂ exhibited higher overpotential values. Novelty: The study provides a comparative evaluation linking synthesis routes, nanostructure morphology, and HER electrocatalytic behavior of two nickel-based catalysts. Implications: These findings support the development of scalable non-precious metal catalysts for alkaline water electrolysis and sustainable hydrogen production technologies. Highlights:• Porous Nanosheet Architecture Provides High Electrochemically Active Surface Area.• Charge Transfer Resistance Decreases at the Catalyst and Electrolyte Interface.• Long-Term Operation Exceeding Fifty Hours Demonstrates Durability in Alkaline Medium. Keywords: Nickel Based Nanocatalysts, Hydrogen Evolution Reaction, Alkaline Water Splitting, Electrocatalysis, Nanostructured Catalysts